Las memorias del visitador, la relación picaresca y la ceguera colonial en «El lazarillo de ciegos caminantes» (1773): una lectura reparativa - Folger, Robert (RILCE, 2025)
Most interpretations of El Lazarillo de ciegos caminantes (1773 [1775/76]) are guided by a hermeneutics of suspicion, which unmasks the spurious attribution of the work to the narrator Calixto Bustamante Carlos Inca alias Concolorcorvo as a hoax and attributes voice and meaning exclusively to the «real» author, the Spaniard Alonso Carrió de la Vandera. In an attempt not to reproduce «paranoically» the epistemology and ideology that shape the text, a reparative reading (Sedgwick) of the Lazarillo neither rejects nor disqualifies the narrator but rather acknowledges his presence and agency. This reparative reading reveals the blind spot of colonial rule and the impossibility of writing a counter-hegemonic history of colonialism instead of recovering a subaltern voice.